Traditional Round Robin CPU Scheduling Algorithm to Prioritize Processes with Residual Burst time Nearest to the Specified time Quantum: An Advanced Approach - Mythili Boopathi; Pranav Korde; Pallav Dey (Novel Perspectives of Engineering Research Vol. 5, 2022)
The purpose of this paper is to introduce an optimised variant to the round robin scheduling algorithm. The Round Robin scheduling algorithm is one of the most widely used CPU scheduling algorithms, and it is used in a variety of software systems. Every algorithm works in its own way and has its own merits and demerits. The proposed algorithm overcomes the shortfalls of the existing scheduling algorithms in terms of waiting time, turnaround time, throughput and number of context switches. The algorithm is pre-emptive and works based on the priority of the associated processes. The priority is decided on the basis of the remaining burst time of a particular process, that is; lower the burst time, higher the priority and higher the burst time, lower the priority. To complete the execution, a time quantum is initially specified. In case if the burst time of a particular process is less than 2X of the specified time quantum but more than 1X of the specified time quantum; the process is given high priority and is allowed to execute until it completes entirely and finishes. Such processes do not have to wait for their next burst cycle.